An integrated disease-specific graded prognostic assessment scale for melanoma: contributions of KPS, CITV, number of metastases, and BRAF mutation status. Issue 1 (12th November 2020) - Ahluwalia, Manmeet; Ali, Mir A; Joshi, Rushikesh S; Park, Eun Suk; Taha, Birra; McCutcheon, Ian; Chiang, Veronica; Hong, Angela; Sinclair, Georges; Bartek, Jiri; Chen, Clark C
Abstract: Background: Stereotactic radiosurgery (SRS) remains a mainstay therapy in the treatment of melanoma brain metastases (BM). While prognostic scales have been developed for melanoma patients who underwent SRS treatment for BM, the pertinence of these scales in the context of molecularly targeted therapies remains unclear. Methods: Through a multi-institutional collaboration, we collated the survival patterns of 331 melanoma BM patients with known BRAF mutation status treated with SRS. We established a prognostic scale that was validated in an independent cohort of 174 patients. All patients with BRAF mutations in this series were treated with BRAF inhibitors. Prognostic utility was assessed using Net Reclassification Index (NRI > 0) and integrated discrimination improvement (IDI) metrics. Results: In a multivariate Cox proportional hazards model, BRAF mutation status, KPS, number of metastases, and cumulative intracranial tumor volume (CITV) independently contributed to survival prognostication for melanoma patients with SRS-treated BM ( P < .05 for all variables). These variables were incorporated into a prognostic scale using the disease-specific graded prognostic assessment (ds-GPA) framework. This integrated melanoma ds-GPA scale was validated in 2 independent cohorts collated through a multi-institutional collaboration. In terms of order of prognostic importance, BRAF mutation status exerted the greatest influence on survival, while KPS, the number of metastases, and CITV exhibited comparable, lesser impacts. Conclusions: Optimal survival prognostication for SRS-treated patients with melanoma BM requires an integrated assessment of patient characteristics (KPS), tumor characteristics (CITV and number of metastases), and the mutational profile of the melanoma (BRAF mutation status).